Simulating PACE Global Ocean Radiances - Gregg, Watson W.; Rousseaux, Cécile S. (Frontiers in Marine Science, 2017)
The NASA PACE mission is a hyper-spectral radiometer planned for launch in the next decade. It is intended to provide new information on ocean biogeochemical constituents by parsing the details of high resolution spectral absorption and scattering. It is the first of its kind for global applications and as such, poses challenges for design and operation. To support pre-launch mission development and assess on-orbit capabilities, the NASA Global Modeling and Assimilation Office has developed a dynamic simulation of global water-leaving radiances, using an ocean model containing multiple ocean phytoplankton groups, particulate detritus, particulate inorganic carbon (PIC), and chromophoric dissolved organic carbon (CDOC) along with optical absorption and scattering processes at 1nm spectral resolution. The purpose here is to assess the skill of the dynamic model and derived global radiances. Global bias, uncertainty, and correlation are derived using available modern satellite radiances at moderate spectral resolution. Total chlorophyll, PIC, and the absorption coefficient of CDOC (aCDOC), are simultaneously assimilated to improve the fidelity of the optical constituent fields. A five-year simulation showed statistically significant (P<0.05) comparisons of chlorophyll (r=0.869), PIC (r=0.868), and aCDOC (r=0.890) with satellite data. Additionally, diatoms (r=0.890), cyanobacteria (r=0.732), and coccolithophores (r=0.716) were significantly correlated with in situ data. Global assimilated distributions of optical constituents were coupled with a radiative transfer model (Ocean-Atmosphere Spectral Irradiance Model, OASIM) to estimate normalized water-leaving radiances at 1nm for the spectral range 250nm to 800nm. These unassimilated radiances were within -0.074 mW cm-2 µm-1 sr-1 of MODIS-Aqua radiances at 412, 443, 488, 531, 547 and 667nm. This difference represented a bias of -10.4% (model low). A mean correlation of 0.706 (P<0.05) was found with global distributions of MODIS radiances. These results suggest skill in the global assimilated model and resulting radiances. The reported error characterization suggests that the global dynamical simulation can support some aspects of mission design and analysis. For example, the high spectral resolution of the simulation supports investigations of band selection. The global nature of the radiance representations supports investigations of satellite observing scenarios. Global radiances at bands not available in current and past missions support investigations of mission